Perbandingan Pengajaran Keterampilan Berbicara Bahasa Arab dan Bahasa Inggris di Sekolah Tinggi Agama Islam Negeri Curup - Aflisia, Noza; Harahap, Partomuan (Institut Agama Islam Negeri Curup, 2017)
At STAIN Curup, Arabic development is not as fast as English development. This can be seen from the holding of international seminars by presenting speakers from Middle Eastern countries but the language used in the seminar is English. Students' interest in admission to the English Tadris Study Program is higher than that of the Arabic Education Studies Program. They consider English easier than Arabic. This research focuses more on the implementation of teaching Arabic and English in STAIN Curup covering objectives, materials, methods, media and evaluation. The research method used is descriptive qualitative. Data collection uses observation, interviews, and documentation. Data analysis techniques are data reduction, data display, data analysis, and narrative analysis results. The research result is Muhadatsah teaching and Speaking teaching equally train the students ability in using those languages in communication and interaction with the other person. In teaching not only using the book as a reference but also gives freedom to students in practicing foreign languages by finding new ideas outside reference books that are used as a reference. The learning of Muhadatsah and Speaking in STAIN Curup is Student Centris, by presenting various methods. In learning Muhadatsah only utilize audio media, while in learning Speaking in addition to audio media also use audio-visual media. Overall it can be seen that the teaching of Muhadatsah and Speaking as the teaching of Arabic and English speaking skills is emphasized by the learning process that is learning rather than emphasizing the evaluation.